The complete chloroplast genome of Morus alba (Moraceae: Morus), the herbal medicine species in China - Jiang Luo; Yingying Wang; Allan ZiJian Zhao (Mitochondrial DNA. Part B. Resources, 2019)
Morus alba is commonly called white mulberry, which is native to China and is the tender branch of mulberry as a herbal medicine in China. In this study, we presented and annotated the complete chloroplast genome of M. alba. The whole chloroplast genome is 159,050 bp in size, exhibiting a large single copy region (87,762 bp), a small single-copy region (19,876 bp) and a pair of inverted-repeat regions (25,706 bp). The overall nucleotide composition is: 31.4% of A, 32.4% of T, 18.4% C, and 17.8% G, with a total A + T content of the chloroplast genome 63.8% and G + C content of 36.2%. The whole chloroplast genome of M. alba contains 126 genes, including 82 protein-coding genes (PCG), 36 transfer RNA (tRNAs), and 8 ribosome RNA (rRNAs). Phylogenetic Maximum-Likelihood (ML) tree based on 15 species chloroplast genomes that Morus alba is closely related to Morus cathayana. This complete chloroplast genomes can be used for medicinal value and clinical drug development that also can have a great significance for future to continue research.